Radiology in global health : strategies, implementation, and applications - Lungren, Matthew P.; Mollura, Daniel J. (Springer New York, 2014)
This book is designed to increase awareness of the global health problem of lack of access to medical imaging services and presents solutions to overcome disparities in the delivery of radiologic services to the developing world. Featuring an interdisciplinary framework, it discusses economic strategies for sustainable radiology; public health radiology for population-based approaches; clinical model formulation tailored to needs and resources of regions and communities; technology innovation and optimization; and public policy for healthcare system development at the government and international institutional level.   It explores the role of radiology in addressing health care disparities and highlights strategies for radiology services planning and implementation in low resource settings. It also provides an overview of the clinical role of medical imaging in the developing world, including epidemiology, disaster response, and specific clinical applications for recognizing and managing illnesses unique to the developing world. Radiology in Global Health: Strategies, Implementation, and Applications examines ways to achieve sustainable long-term imaging strategies for limited resource regions and is a valuable resource for radiologists, radiology residents, radiology technologists, physicians, nurses, and  healthcare administrators.